2018
DOI: 10.21303/2461-4262.2018.00639
|View full text |Cite
|
Sign up to set email alerts
|

The Overview of Investigation in the Field of Banknote Design for Visually Impaired People

Abstract: This essay aims to elaborate the technology when it comes to banknote making for visually impaired members of the society. The visually impaired are divided in three subgroups: color-blind, partially sighted and blind people. Their first needs are useful denomination features rather than security features, as they help them in determining a banknote's value. This study provides a historical overview of banknote design features for the visually impaired. Furthermore, it looks into the methodology of banknote te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…Papers [2,3] describe the main elements of highly protected products, which allow all groups of the population, in particular people with visual impairments, to identify the denomination of banknotes and the authenticity of protected products. A special role among such elements is played by relief, tactilely recognizable design elements -MPVI, applied by intaglio printing and/or colorless embossing, and high contrast of the printed background and the image to be identified.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Papers [2,3] describe the main elements of highly protected products, which allow all groups of the population, in particular people with visual impairments, to identify the denomination of banknotes and the authenticity of protected products. A special role among such elements is played by relief, tactilely recognizable design elements -MPVI, applied by intaglio printing and/or colorless embossing, and high contrast of the printed background and the image to be identified.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Setiap negara, termasuk Indonesia, memiliki caranya sendiri untuk mengatasi masalah ini. Dalam praktiknya di harapkan bahwa secara bertahap dapat ditemukan suatu solusi baru yang memberi lebih banyak kesempatan bagi mereka yang tidak memiliki kondisi normal untuk menjalani kehidupan (Kyrychok, 2018), misalnya penemuan-penemuan terbaru baik yang berbentuk teknologi secara fisik, maupun pengembangan kemampuan secara non fisik, yang dapat dilakukan secara bersamasama oleh pemerintah dan masyarakat, demi terciptanya aksesibilitas disabilitas netra dalam mengenali uang kertas rupiah.…”
Section: Komunikasi Pesan Melalui Kegiatan Sosialisasiunclassified
“…Analysis of papers [1][2][3][4][5][6] and descriptions of banknotes available on the official websites of state banks of the world allowed to determine the main methods of ensuring the possibility of identifying the denomination of banknotes by people with various visual impairments. The conducted analysis showed that about 73% of countries use special tactile recognition elementsbanknotes marks for people with visual impairments (MPVI)as the main element of tactile identification of the denomination of printed banknotes.…”
Section: Introduction 11 Problem Statementmentioning
confidence: 99%